FcγR mediates TLR2- and Syk-dependent NLRP3 inflammasome activation by inactivated Francisella tularensis LVS immune complexes - Duffy, Ellen B. (J Leukoc Biol, 2016)
IgG (mAb)-opsonized, inactivated Francisella tularensis LVS (iFt-mAb) enhances TLR2-dependent IL-6 production by macrophages via Fcγ receptors (FcγR). In mice, vaccination with iFt-mAb provides IgA-dependent protection against lethal challenge with Ft LVS. Because inflammasome maturation of IL-1β is thought important for antibody-mediated immunity, we considered the possibility that iFt-mAb elicits an FcγR-dependent myeloid cell inflammasome response. Herein, we find that iFt-mAb enhances macrophage and dendritic cell IL-1β responses in a TLR2- and FcγR-dependent fashion. Although iFt-mAb complexes bind FcγR and are internalized, sensing of cytosolic DNA by absent in melanoma 2 (AIM2) is not required for the IL-1β response. In contrast, ASC, caspase-1, and NLR family pyrin domain-containing 3 (NLRP3) are indispensable. Further, FcγR-mediated spleen tyrosine kinase (Syk) signaling is required for this NLRP3-dependent IL-1β response, but the alternative IL-1β convertase caspase-8 is insufficient. Finally, iFt-mAb-vaccinated wild-type mice exhibit a significant delay in time to death, but IL-1R1– or Nlrp3-deficient mice vaccinated in this way are not protected and lack appreciable Francisella-specific antibodies. This study demonstrates that FcγR-mediated Syk activation leads to NLRP3 inflammasome-dependent IL-1β production in macrophages and suggests that an Nlrp3- and IL-1R–dependent process contributes to the IgA response important for protection against Ft LVS. These findings extend our understanding of cellular responses to inactivated pathogen-opsonized vaccine, establish FcγR-elicited Syk kinase-mediated NLRP3 inflammasome activation, and provide additional insight toward understanding crosstalk between TLR and FcγR signals.